2020
DOI: 10.4187/respcare.07362
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Nebulizer Drying for Patients With Cystic Fibrosis

Abstract: BACKGROUND: Nebulizer therapy is an important treatment component for patients with cystic fibrosis (CF). Nebulizer manufacturers' guidelines advocate thorough nebulizer drying after washing. The aim of this study, therefore, was to examine the microbiology associated with nebulizer drying, particularly related to Pseudomonas control, and to examine microbiologically non-adherence to the recommended drying procedures. METHODS: Four aspects of nebulizer drying were examined in 3 common nebulizers, including exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…In all cases, the outbreak strains persisted in all milieux for at least one week. Persistence behaviour of these outbreak strains are very much different from recently described P. aeruginosa clinical isolates from the sputum of patients with CF, which were unable to survive 24 h, under similar desiccation conditions (Moore et al, 2020). The relative persistence of the outbreak strains in this neonatal outbreak may therefore be considered an important aspect of their biology and a virulence factor, in prolonging strain survival in the environment and potentially outbreak duration.…”
Section: Discussioncontrasting
confidence: 79%
“…In all cases, the outbreak strains persisted in all milieux for at least one week. Persistence behaviour of these outbreak strains are very much different from recently described P. aeruginosa clinical isolates from the sputum of patients with CF, which were unable to survive 24 h, under similar desiccation conditions (Moore et al, 2020). The relative persistence of the outbreak strains in this neonatal outbreak may therefore be considered an important aspect of their biology and a virulence factor, in prolonging strain survival in the environment and potentially outbreak duration.…”
Section: Discussioncontrasting
confidence: 79%
“…This scenario would simulate the maximum numbers of organisms contaminating the mouthpiece and therefore the greatest challenge to disinfector efficiency. Given that the outside of the mouthpiece is never in contact with secretions from the player, this was not emulated in this experiment and therefore we focussed solely on emulating wet surfaces on the inner bore of the mouthpiece, as drying has been recently shown to kill Pseudomonas aeruginosa on surfaces (Moore et al 2020). These Gram-positive and Gram-negative organisms were selected, as important clinical organisms, as well as surrogates for other opportunistic pathogens that may be found in players' saliva, as part of the normal flora of the mouth, upper respiratory tract and upper gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by M oore et al [ 71 ] examined the effect of drying on P. aeruginosa and showed that there were marked differences in time to complete dryness between disassembled and fully assembled nebulisers. Vigorous repeated shaking was unable to drive off all residual water on assembled nebulisers.…”
Section: Dryingmentioning
confidence: 99%
“…Equally, this study showed that if the device is not dried thoroughly and moisture remains, then the device is able to support the survival of P. aeruginosa at high numbers, constituting an infection risk to the CF patient. These data may help educate and inform the CF patient about the importance of proper nebuliser drying for Pseudomonas control, in order to improve patient awareness and safety [ 71 ]. More recently, there have been two reports demonstrating that members of the NTM, Mycobacterium abscessus complex and S. aureus (methicillin-sensitive and -resistant) can survive for at least 24 h on plastic surfaces during air drying [ 72 , 73 ].…”
Section: Dryingmentioning
confidence: 99%